2021
DOI: 10.1101/2021.06.08.447644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced virus translation enables miR-122-independent Hepatitis C Virus propagation

Abstract: The 5’UTR of the Hepatitis C Virus genome forms RNA structures that regulate virus replication and translation. The region contains a viral internal ribosomal entry site and a 5’ terminal region. Binding of the liver specific miRNA, miR-122, to two conserved binding sites in the 5’ terminal region regulates viral replication, translation, and genome stability, and is essential for efficient virus replication, but its precise mechanism of its action is still under debate. A current hypothesis is that miR-122 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…However, several studies on miR-122-independent replication also showed virus replication in Dicer and Drosha knockout cells, which are devoid of miRNAs that rely on the canonical miR-122 biogenesis pathways. HCV-S2-GGCGUG which has been reported previously for replicating in the absence of miR-122 was capable of replicating in Dicer KO Huh 7.5 cells, and several mutants were shown to replicate in Drosha knockout cells [19,65]. Additionally, another study showed that Ago2 interaction with HCV genome was not detected for miR-122independent replication of G28A, suggesting that miR-122 independent replication of HCV is not because of the binding of other microRNAs to the 5 UTR of the viral RNA and no other microRNA compensate for miR-122-independent replication of G28A HCV [71].…”
Section: Mechanism Of Mir-122-independent Replication 71 Replication ...mentioning
confidence: 68%
See 4 more Smart Citations
“…However, several studies on miR-122-independent replication also showed virus replication in Dicer and Drosha knockout cells, which are devoid of miRNAs that rely on the canonical miR-122 biogenesis pathways. HCV-S2-GGCGUG which has been reported previously for replicating in the absence of miR-122 was capable of replicating in Dicer KO Huh 7.5 cells, and several mutants were shown to replicate in Drosha knockout cells [19,65]. Additionally, another study showed that Ago2 interaction with HCV genome was not detected for miR-122independent replication of G28A, suggesting that miR-122 independent replication of HCV is not because of the binding of other microRNAs to the 5 UTR of the viral RNA and no other microRNA compensate for miR-122-independent replication of G28A HCV [71].…”
Section: Mechanism Of Mir-122-independent Replication 71 Replication ...mentioning
confidence: 68%
“…Further, knocking down of RNA degrading enzymes rescued replication of several mutants, some to miR-122-dependent levels, suggesting that the roles of miR-122 can be compensated by enhancing virus translation and stabilizing the viral genome. Experiments also demonstrated that enhanced translation rescued viral replication by approximately 100-fold, whereas enhanced stability rescued viral replication approximately 10-fold, and suggested that the major role for miR-122 is translation stimulation with stabilization being important but less potent [65].…”
Section: Utr Mutations Modulate the 5 Utr Rna Structure And Stimulate...mentioning
confidence: 98%
See 3 more Smart Citations